SERANGAN MONGOL DAN TIMUR LENK SERTA DAMPAKNYA TERHADAP DAKWAH ISLAMIYYAH DI DINASTI ABBASIYYAH - Harjani Hefni (Khatulistiwa, 2014)
The period early 7th century AH (13 AD), keeps its own meaning for the Islamic world. After six centuries of expansion with its various dynamics, the land of Muslims, with the Abbasiyyah Dynasty as its symbol entered the 7th century like a body stricken with severe flu virus. While the condition was not fit, it was attacked insistently by outside parties, beginning with the Crusades and continued with Mongol attacks. The weak body finally collapsed, unconscious for some time before being able to get up. The most disastrous blow befell the Muslims was the attack that was launched by the Mongols. In a relatively short time, almost all Muslim countries were ruled by the Mongols. This paper will examine the lives of the Mongols, the reasons for attacking Muslim countries, the factors that cause the defeat of the Muslims, the impact of the attacks on the religious life and activities da'wah and some analysis about the events.